FACTORS INFLUENCING STRATEGIC USE OF WEBBASED PLATFORM AND ITS IMPACT ON EDUCATION AT UNIVERSITY - Vasiljeva, Tatjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Introducing web-based platforms in education process opens new era of technology for learning including huge challenges in education. Web-based learning could be considered as essential component fostering online learning and teaching. Various factors influencing the teachers while applying study materials in e-learning platform are investigated in the given research study. The author offers an indicative pattern of a standard content of eteaching materials, and investigates to what extent teaching materials available in MOODLE correspond to this standard pattern for ensuring comprehensive web-based e-learning and supporting effective collaboration system for the students and educator. For assessment the completeness level of e-materials available the composite coefficient is recommended as useful tool for educators who are interested in developing e-learning and e-teaching.